2020
DOI: 10.1016/j.compositesa.2019.105714
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and investigation on ternary heterogeneous MWCNT@TiO2-C fillers and their silicone rubber wave-absorbing composites

Abstract: Ternary heterogeneous MWCNT@TiO 2-C wave absorbent was firstly prepared, using glucose, MWCNT, and titanium isopropoxide as raw materials, through the solvothermal process followed by post-heat treatment. Afterwards, MWCNT@TiO 2-C/silicone rubber wave-absorbing composites were fabricated via solution casting and subsequent curing process. XRD, Raman, XPS, and TEM analyses demonstrated the MWCNT@TiO 2-C fillers were successfully synthesized with TiO 2 and amorphous carbon coated on the surface of MWCNT. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(36 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…[ 48–50 ] The crystalline state of carbon in SCFs was almost the same between SCF@GO and SCF@CNTs hybrids as there is negligible difference between the values of R for both cases. [ 51 ] This confirmed that both GO and CNTs were successfully assembled onto the surface of SCFs, which was also corroborated by SEM.…”
Section: Resultssupporting
confidence: 66%
“…[ 48–50 ] The crystalline state of carbon in SCFs was almost the same between SCF@GO and SCF@CNTs hybrids as there is negligible difference between the values of R for both cases. [ 51 ] This confirmed that both GO and CNTs were successfully assembled onto the surface of SCFs, which was also corroborated by SEM.…”
Section: Resultssupporting
confidence: 66%
“…On the high-resolution spectrum of O 1 s of S-5 (Fig. 4 d), three characteristic peaks of 531.5, 530.6, and 529.0 eV can be observed, corresponding to the water or O adsorbed on the sample surface, oxygen vacancies and metal-O (Ni–O/Co–O) respectively [ 49 , 50 ]. Co 2p can be fitted to six distinct characteristic peaks (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at 1000 cm −1 belonged to the C-O stretching mode. While the measurement of XRD clearly indicates that the TiO 2 is highly crystallized, this phenomenon may be described as the formation of C-O-Ti bond in the TiO 2 /graphene system [34,35]. The FT-IR spectrum of Ag/TiO 2 /graphene is similar to that of TiO 2 / graphene, which suggests that loading Ag nanowires will not change the chemical structure of TiO 2 /graphene nanocomposite.…”
Section: Antibacterial Performancementioning
confidence: 95%